Human Cerebral Cortex Proteome of Fragile X-Associated Tremor/Ataxia Syndrome - Holm, Katharine Nichole; Herren, Anthony W.; Taylor, Sandra L.; Randol, Jamie L.; Kim, Kyoungmi; Espinal, Glenda; Martínez-Cerdeño, Verónica; Pessah, Isaac N.; Hagerman, Randi J.; Hagerman, Paul J. (Frontiers in Molecular Biosciences, 2021)
Background: Fragile X-associated tremor/ataxia syndrome (FXTAS) is an adult-onset neurodegenerative disorder associated with premutation CGG-repeat expansions (55–200 repeats) in the 5′ non-coding portion of the fragile X mental retardation 1 (FMR1) gene. Core features of FXTAS include progressive tremor/ataxia, cognitive decline, variable brain volume loss, and white matter disease. The principal histopathological feature of FXTAS is the presence of central nervous system (CNS) and non-CNS intranuclear inclusions. Objective: To further elucidate the molecular underpinnings of FXTAS through the proteomic characterization of human FXTAS cortexes. Results: Proteomic analysis of FXTAS brain cortical tissue (n = 8) identified minor differences in protein abundance compared to control brains (n = 6). Significant differences in FXTAS relative to control brain predominantly involved decreased abundance of proteins, with the greatest decreases observed for tenascin-C (TNC), cluster of differentiation 38 (CD38), and phosphoserine aminotransferase 1 (PSAT1); proteins typically increased in other neurodegenerative diseases. Proteins with the greatest increased abundance include potentially novel neurodegeneration-related proteins and small ubiquitin-like modifier 1/2 (SUMO1/2). The FMRpolyG peptide, proposed in models of FXTAS pathogenesis but only identified in trace amounts in the earlier study of FXTAS inclusions, was not identified in any of the FXTAS or control brains in the current study. Discussion: The observed proteomic shifts, while generally relatively modest, do show a bias toward decreased protein abundance with FXTAS. Such shifts in protein abundance also suggest altered RNA binding as well as loss of cell–cell adhesion/structural integrity. Unlike other neurodegenerative diseases, the proteome of end-stage FXTAS does not suggest a strong inflammation-mediated degenerative response.